Komunikasi Islam dalam Membangun Etika Bermedia Sosial di Era Digital - Meysarah (4, 2026)
The development of information and communication technology in the digital era has brought about significant changes in people's interaction patterns, particularly in the use of social media. The presence of various digital platforms such as WhatsApp, Instagram, Facebook, and TikTok has made it easier to disseminate information and communicate without the constraints of time and space. However, these developments have also given rise to various ethical issues, such as the spread of hoaxes, hate speech, cyberbullying, slander, and low levels of politeness in social media communication. This study aims to analyze the role of Islamic communication in developing social media ethics in the digital era. This study used a qualitative approach with library research. Data were obtained through a review of the Quran, Hadith, books, scientific journals, and various other literature relevant to Islamic communication and social media ethics. Data analysis was conducted using descriptive qualitative techniques through the stages of data reduction, data presentation, and conclusion drawing. The research results show that Islamic communication encompasses ethical principles that are highly relevant to the use of social media, such as qaulan sadidan (correct speech), qaulan ma'rufa (good speech), qaulan layyina (gentle speech), and the principle of tabayyun (verification of information before disseminating it). Islamic communication values ​​can serve as moral guidelines in creating a culture of polite, wise, and responsible digital communication. Furthermore, Islamic communication also plays a role in raising public awareness to utilize social media as a means of da'wah, education, and the dissemination of good values. Thus, the application of Islamic communication in the digital era is expected to create a more harmonious, peaceful, and dignified social media space in accordance with Islamic teachings. Abstrak Perkembangan teknologi informasi dan komunikasi di era digital telah membawa perubahan besar terhadap pola interaksi masyarakat, khususnya dalam penggunaan media sosial. Kehadiran berbagai platform digital seperti WhatsApp, Instagram, Facebook, dan TikTok memberikan kemudahan dalam penyebaran informasi dan komunikasi tanpa batas ruang dan waktu. Namun, perkembangan tersebut juga menimbulkan berbagai persoalan etika, seperti penyebaran hoaks, ujaran kebencian, cyberbullying, fitnah, dan rendahnya kesantunan dalam berkomunikasi di media sosial. Penelitian ini bertujuan untuk menganalisis peran komunikasi Islam dalam membangun etika bermedia sosial di era digital. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research). Data diperoleh melalui kajian terhadap Al-Qur’an, hadis, buku, jurnal ilmiah, dan berbagai literatur yang relevan dengan komunikasi Islam dan etika media sosial. Teknik analisis data dilakukan secara deskriptif kualitatif melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa komunikasi Islam memiliki prinsip-prinsip etika yang sangat relevan dalam penggunaan media sosial, seperti qaulan sadidan (perkataan yang benar), qaulan ma’rufa (perkataan yang baik), qaulan layyina (perkataan yang lemah lembut), serta prinsip tabayyun dalam memverifikasi informasi sebelum menyebarkannya. Nilai-nilai komunikasi Islam mampu menjadi pedoman moral dalam menciptakan budaya komunikasi digital yang santun, bijak, dan bertanggung jawab. Selain itu, komunikasi Islam juga berperan dalam membangun kesadaran masyarakat agar memanfaatkan media sosial sebagai sarana dakwah, pendidikan, dan penyebaran nilai-nilai kebaikan. Dengan demikian, penerapan komunikasi Islam di era digital diharapkan dapat menciptakan ruang media sosial yang lebih harmonis, damai, dan bermartabat sesuai dengan nilai-nilai ajaran Islam.